Declined contrast sensitivity of neurons along the visual pathway in aging cats - Wang, Zhengchun; Yao, Zhimo; Yuan, Nini; Liang, Zhen; Li, Guangxing; Zhou, Yifeng (Frontiers in Aging Neuroscience, 2014)
Changes in the visual cortex appear to mediate much of the visual degradation during normal aging. However, how aging affects different stages along the visual pathway is unclear. In the current study, the contrast response function, one of the most important properties of neurons from early visual areas to high brain areas, was systematically compared along the visual pathway, including the lateral geniculate nucleus (LGN), early visual cortices (A17 and A18), and posteromedial lateral suprasylvian cortex [PMLS, analog to the medial temporal area (MT) in monkeys] of young and old cats. We found that the effects of aging on the LGN were negligible, whereas those in the striate cortex were substantial, with even more severe degradation in the PMLS. Reduced contrast sensitivity of neurons in the three cortical areas was accompanied by enhanced maximal visual response, increased spontaneous activity, and decreased signal-to-noise ratio, while LGN neurons exhibited largely normal response properties. Our results suggested that there was a progressively greater effect of aging on neurons at successively higher stages in the visual pathway.